Understanding public perceptions of marine threats: awareness and concern among residents and visitors of the German Baltic Sea Coast - Demmler, Rebecca A.; Stoll-Kleemann, Susanne (Frontiers in Marine Science, 2025)
The ecosystem of the Baltic Sea fulfills important functions for the ecological and socio-economic well-being of its surrounding region and human well-being. However, it faces severe threats from human activities, such as hazardous substances, eutrophication, habitat degradation or overfishing which have led to a concerning ecological state of the basin. Public perceptions can provide valuable insights into promoting behavioral change and support for marine conservation strategies. This study examines public perceptions of environmental threats to the Baltic Sea ecosystem among residents and visitors of the Island of Ruegen and the Greifswalder Bodden. Data were collected by employing face-to-face interviews (N = 628). Residents and visitors reported high levels of awareness and concern about ecological threats to the Baltic Sea. Yet, they did not accurately assess the ecosystem’s poor condition and most frequently identified highly visible threats such as plastic waste or oil spills. Less perceptible and more complex issues, like climate change, biodiversity loss, heavy metals or noise pollution were mentioned infrequently. Participants’ perceptions varied according to their proximity of residence to the coast, age and current engagement in educational contexts. It may be further assumed that media coverage, local historical and socio-economic contexts, as well as various personal and psychological factors, contribute to shaping public understanding. The findings suggest that effective marine conservation in the Baltic Sea region may be strengthened by correcting prevalent misconceptions and promoting comprehensive, evidence-based information that also resonates on an emotional level. To support this, it may be beneficial to actively involve local communities and cultivate deeper, more personal connections between the public and the marine environment.